Study of the Link Between Neuronal Death, Glial Response, and MAPK Pathway in Old Parkinsonian Mice - Gil-Martinez, Ana Luisa; Cuenca-Bermejo, Lorena; Gallo-Soljancic, Pablo; Sanchez-Rodrigo, Consuelo; Izura, Virginia; Steinbusch, Harry W. M.; Fernandez-Villalba, Emiliano; Herrero, Maria Trinidad (Frontiers in Aging Neuroscience, 2020)
Background: Parkinson’s disease (PD) is described as an age-related neurodegenerative disorder. However, the vast majority of research is carried out using experimental models of young animals lacking the implications of the decline processes associated with aging. It has been suggested several molecular pathways that are involved in the perpetuation of the degeneration and the neuroinflammation in PD. Among others, mitogen-activated protein kinases (MAPKs) have been highly implicated in the development of PD and regulating components of their activity are indicated as promising therapeutic targets. Methods: To further define how MAPKs expression is related to the glial responses and neuronal cell death, Parkinsonism was induced under an acute regimen in old mice. Moreover, the sacrifice was carried out at different time points (4h, 8h, 24h and 48h) after MPTP injections to describe the early dynamic changes over time produced by the intoxication. Results: The results revealed that neuronal death increases as glial response increases in the nigrostriatal pathway. It was observed that both processes increase from 4h in the ventral mesencephalon and neuronal death become significantly from 48h. In the striatum, they were significantly increased from 48h after the MPTP administration compared with the control mice. Moreover, p-ERK levels decrease while phospho-p38 expression increases specifically in the striatum from 48h after MPTP intoxication. Conclusions: The importance of these data lies in the possibility of elucidating the underlying mechanisms of neurodegenerative processes under aging conditions to provide knowledge for the search of solutions that slow down the progression of PD.